2006
DOI: 10.1163/157075406778116186
|View full text |Cite
|
Sign up to set email alerts
|

Deformities in cane toad (Bufo marinus) populations in Bermuda: Part III. Microcosm-based exposure pathway assessment

Abstract: Short-term embryo-larval, limb development, and a battery of toxicity identification studies using sediment and water collected from selected ponds found that developmentally toxic samples contained elevated levels of petroleum hydrocarbons and As, Cu, Pb, Cr, Cd, Hg, Fe, and Zn. Sediments spiked with diesel fuel or metals confirmed that the levels of petroleum hydrocarbons and metals found in the sediment were capable of inducing developmental toxicity individually. However, joint mixture interaction studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…The only record in Brazilian anurans was in hybrids of Rhinella icterica (Spix, 1824) with Rhinella crucifer (Wied-Neuwied, 1821), where hybridization seemed to have caused the deformities (Haddad et al 1990). There is evidence that increased rates of microphtalmia in anurans may be caused by exposition to heavy metals (Fort et al 2006). Another possible cause of microphtalmia has been suggested to be caused by Ranavirus FV 3 (Burton et al 2008), but there was no literature on experimental test to evidence it.…”
Section: Introductionmentioning
confidence: 99%
“…The only record in Brazilian anurans was in hybrids of Rhinella icterica (Spix, 1824) with Rhinella crucifer (Wied-Neuwied, 1821), where hybridization seemed to have caused the deformities (Haddad et al 1990). There is evidence that increased rates of microphtalmia in anurans may be caused by exposition to heavy metals (Fort et al 2006). Another possible cause of microphtalmia has been suggested to be caused by Ranavirus FV 3 (Burton et al 2008), but there was no literature on experimental test to evidence it.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, cross-over exposure studies, in which B. marinus embryos from contaminated sites were raised in reference site media and vice versa, showed that there was also a marked maternal effect on larval development and survival. These studies suggested that metals and petroleum hydrocarbons were being transferred from the mother to her eggs during oogenesis and oocyte maturation, and that this transfer of contaminants had a marked impact on larval development and survival (Fort et al, 2006b). In summary, investigations to date indicate that survival and development of B. mar-inus larvae in Bermuda are being affected both by contaminants found in a number of its ponds and by transgenerational transfer of accumulated contaminants.…”
Section: The Amphibiansmentioning
confidence: 98%
“…However, the deformed Boana faber was collected in an area with varying levels of disturbance because the reserve is located in an agricultural matrix where pesticides can accumulate in bodies of water (Tabanez et al 2005). In fact, pesticides are known to cause deformities in embryos and larvae and to produce high rates of eye anomalies in adults (e.g., Bufo marinus; Fort et al 2006).…”
Section: Morphologicalmentioning
confidence: 99%